Mortality Rate at the Brooding Stage of Various Broiler Breeds Reared in Sub Sahara Region of West Africa - Awobajo, O.K.; Grace, O.; Mako, A.A.; Igbosanun, A.O.; Ettu, R.O. (International Journal of Poultry Science, 2009)
The study was based on morality rate at the brooding stage of various broiler breeds reared in Ogun State, Nigeria. The state was divided into four provinces namely Egba, Egbado, Ijebu and Remo Division. The data were collected through the use of questionnaires, 30 questionnaires were administered in each province making 120 Questionnaires in all. The collective data were analyzed with the use of simple percentage, analysis of variance and other statistic techniques. The result shows that there is significant different (p<0.001) in the mortality rate of various broilers breeds during brooding stage with Ross breed having the lowest mortality record, the result also reveal that the major causes of mortality of birds is poor management of the farm, poor feed and feeding, unhygienic environment etc. and the best breed of broiler that is resistance to diseases is Ross breeds of broiler.